Autocrine signaling based selection of combinatorial antibodies that transdifferentiate human stem cells - Xie, Jia; Zhang, Hongkai; Yea, Kyungmoo; Lerner, Richard A. (Proceedings of the National Academy of Sciences - PNAS, 2013)
We report here the generation of antibody agonists from intracellular combinatorial libraries that transdifferentiate human stem cells. Antibodies that are agonists for the granulocyte colony stimulating factor receptor were selected from intracellular libraries on the basis of their ability to activate signaling pathways in reporter cells. We used a specialized “near neighbor” approach in which the entire antibody library and its target receptor are cointegrated into the plasma membranes of a population of reporter cells. This format favors unusual interactions between receptors and their protein ligands and ensures that the antibody acts in an autocrine manner on the cells that produce it. Unlike the natural granulocyte-colony stimulating factor that activates cells to differentiate along a predetermined pathway, the isolated agonist antibodies transdifferentiated human myeloid lineage CD34+ bone marrow cells into neural progenitors. This transdifferentiation by agonist antibodies is different from more commonly used methods because initiation is agenetic. Antibodies that act at the plasma membrane may have therapeutic potential as agents that transdifferentiate autologous cells.